2009
DOI: 10.1073/pnas.0907003106
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs serve as a genetic buffer against genomic shock in Arabidopsis interspecific hybrids and allopolyploids

Abstract: Small RNAs, including microRNAs (miRNAs), small interfering RNAs (siRNAs), and trans-acting siRNAs (tasiRNAs), control gene expression and epigenetic regulation. Although the roles of miRNAs and siRNAs have been extensively studied, their expression diversity and evolution in closely related species and interspecific hybrids are poorly understood. Here, we show comprehensive analyses of miRNA expression and siRNA distributions in two closely related species Arabidopsis thaliana and Arabidopsis arenosa, a natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
296
4
10

Year Published

2012
2012
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(327 citation statements)
references
References 36 publications
17
296
4
10
Order By: Relevance
“…Other reports indicate that alterations to epigenetic systems occur in hybrids (7,17,18). If these systems contribute to heterosis, then a loss of maximum vigor in generations beyond the F1 would be due not only to the segregation of alleles and epialleles but also to possible alterations to the epialleles in the F2 and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reports indicate that alterations to epigenetic systems occur in hybrids (7,17,18). If these systems contribute to heterosis, then a loss of maximum vigor in generations beyond the F1 would be due not only to the segregation of alleles and epialleles but also to possible alterations to the epialleles in the F2 and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…However, crosses between genetically similar parents such as Arabidopsis accessions or subspecies of rice can produce hybrids displaying significant heterosis, apparently breaking down the relationship between genetic distance and extent of hybrid vigor (6, 7). It has been reported that the epigenome evolves at a significantly faster rate than the genetic sequence (8-10), consistent with genetically similar parents having markedly different epigenomes (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These epigenomic systems, such as DNA methylation and small RNAs, play a vital role in genomic stability, development, and the regulation of genes within a plant.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The molecular basis of hybrid incompatibility has been variously attributed to cisor trans-regulatory changes, copy number changes, and amino acid changes (Krüger et al, 2002;Bomblies et al, 2007;Dilkes et al, 2008;, and, thus far, there is little overlap between genes detected in one genus to another (reviewed in Rieseberg and Blackman, 2010). These interactions can affect different targets including pathogen responses (Bomblies et al, 2007;Jeuken et al, 2009;Yamamoto et al, 2010;Mizuno et al, 2011), suppression of transposable elements (TEs) (McClintock, 1984;Shaked et al, 2001;Kashkush et al, 2003;Madlung et al, 2005;Josefsson et al, 2006;Ungerer et al, 2006;Martienssen, 2010), small RNA pathways (Ha et al, 2009;Ng et al, 2012;Shivaprasad et al, 2012;Zhang et al, 2012), and developmental regulatory pathways, such as genomic imprinting in the seed (Josefsson et al, 2006). Importantly, although all these molecular mechanisms have been documented as affected by hybridization in at least one system, their relative contribution to hybrid incompatibility is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This genome shock includes extensive genomic changes as a result of homologous and homeologous pairing, emergence of diverse gene expression patterns and gene redundancy, and transposon activation (Kenan-Eichler et al 2011). A range of rapid genetic and epigenetic alterations accompanying allopolyplodization have been reported, such as DNA arrangement (Pires et al 2004;Pontes et al 2004), changes in chromosome number (Negron-Ortiz 2007) and structure (Lim et al 2008), gain or loss of DNA (Song et al 1995), transposon activation (Zhang et al 2013;Zou et al 2011), transcriptome shock (Hegarty et al 2006), and epigenetic alterations such as methylation (Lukens et al 2006;Zhang et al 2013), histone modifications and variants (Madlung and Wendel 2013), and small RNA change (Ha et al 2009;Kenan-Eichler et al 2011). …”
Section: Introductionmentioning
confidence: 99%